INTENSIFICATION OF DUST GAS CLEANING PROCESS - Ergashev Nasimbek Akhmadjonovich; Isomidinov Azizjon Salomidinovich; Madaliyev Akhrorbek Niyzomidin ogli; Ummatov Rustambek Bektoshevich; Xonazarov Roʼzimuhammad Dilshodjon oʼgʼli (American Journals Publishing, 2022)
The article provides information on the processes of cleaning various heterogeneous waste generated in the production processes of industrial enterprises and the basis of their selection of the types of constructions suitable for the process. Based on the physico-chemical characteristics of the generated heterogeneous wastes, the issues of selecting cleaning devices were considered. There was also talk about the trend of wet cleaning devices.
Keywords: wet method, gas mixture, heterogeneous, tendency, sedimentation under the influence of gravity, centrifugal, sedimentation in electric and other force field, filter, washing of gases.